Optimization Production System Catching and Fish Processing At Kub (Kelompok Usaha Bersama) Sinar Rohil - Ciary Jannah Mangkay; Fajar Restuhadi; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this study is to analyze the combination of catching and processing fish products are appropriate in order to achieve optimal conditions and analyze the allocation of resources owned by the firm to achieve optimal conditions. This research was conducted in Desember 2012 to July 2013 with a survey method. direct interviews with employees KUB (Kelompok usaha bersama) sinar rohil both on land and at sea as well as direct observation of the field conditions where the authors study This research aims to provide information about the activities of the optimization of production systems at the company Data processing method uses operations research techniques with linear programming aided by software QM for windows. Refined analysis of process data can be viewed through 3 stages: analysis of primal, dual analysis and sensitivity analysis. The activities of production management are fishing operations in the fishing ground and processing the fish on land The result of optimization calculation on 15 GT vessels show that in optimum condition system cathching and fish processing black fomfret weighing 2.959 kg , silver fomfret 6.315 kg, and torpedo scad weighing 5.614 kg that give profit to the company. While excessive resources or resource constraints become inactive is fuel, bait, operational budget, budget marine workers, auxiliary raw materials, labor and drying place. Keywords: Optimization, System Catching, Linear Programming